VASILY EROSHENKO AS FOUNDER AND HEADMASTER OF THE FIRST REPUBLICAN ORPHANAGE FOR BLIND CHILDREN OF THE TURKMEN SSR (1935–1945) - Yuliya V. Patlan (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The article is dedicated to the 130th anniversary of the symbolist author Vasily Eroshenko and the 85th anniversary of the Turkmen School for Blind Children, founded by him. It is the first attempt to bring together and publish three groups of documents regarding Eroshenko’s work in the first Orphanage for Blind Children in Turkmen SSR created at TSSR People’s Commissariat for Education in April, 1935. Firstly, the article includes copies of TSSR People’s Commissariat for Education’s references and acts. Secondly, the memoirs of a nurse Raisa Kisileva, teacher Zinaida Shamina, and children Musa Amansakhatov, Viktor (Vaclav) Brodo, Petr Maloletenko, Valentina Maloletenko, Nurum Momyev, Bainazar Niyazmengliev, and Zoya Tokaeva. Thirdly, we introduce the articles from Turkmen press and the Moscow magazine “Life of the Blind” (1935–38) that tell about the Turkman Orphanage for Blind Children; as well as later articles of 1973–74 containing teachers and students’ memoirs. Those materials were collected in the 1970–90s by blind and sighted enthusiasts of Eroshkin Studies: Anatoly Masenko, Nikolay Osipenko, Alexander Pankov, Albert Polyakovsky and by the members of the “Poisk (Search)” club at the Ashkhabad School for the blind and partially sighted children. The article also presents new names of the orphanage children, discovered by the researchers for Eroshenko’s 100th anniversary. It is for the first time, that Eroshenko’s role of a blind mentor for blind children has been so fully disclosed. We believe that he designed that orphanage school after elementary missionary indigenous schools for the blind built in the British Burma, where he taught in 1917–18. A big difference, however, was the subordination of the school to People’s Commissariat for Education. The main reason why Eroshenko didn’t work long there was a discrepancy between the educational principles borrowed from Protestant missionary schools and the Soviet system of managing orphanages and special schools.